Clinicopathological analysis of 13 patients with embryonal rhabdomyosarcoma of the female reproductive system in the Chinese population - Bai, Liping; Han, Ling; Sun, Liang; Zou, Juan; Chen, Yali (Frontiers in Oncology, 2025)
ObjectiveExamine clinicopathological traits and differential diagnosis of ERMS in female reproductive system.MethodsRetrospectively assess 13 patients’ data (Jan 2018 - Jun 2024, West China Second Univsity Hospital), covering clinical, histological, immunohistochemical aspects and literature review.ResultsAge 2 months - 67 years (median 21), sites in cervix (5), ovaries (3), uterus (2). Non-specific symptoms. Lesions with grape-like etc. morphologies. Immunohistochemistry: the tumor cells expressed Myogenin (11/13), Desmin (13/13), MyoD1 (12/13) and Myoglobin (5/9). 4/5 had DICER1 mutations. According to the Children’s Oncology Group Soft Tissue Sarcoma (COG-STS) risk classification, 11 low risk, 2 high risk. Treatments: 8 surgery + chemotherapy, 2 surgery + chemotherapy + radiotherapy, 2 surgery only. 4 died, 8 survived, 1 lost follow up. Follow-up 2 - 41 months (median 20).DiscussionERMS is rare, diagnosed by histology and immunohistochemistry, DICER1 mutation may assist. Treatment is surgery + chemo ± radiotherapy, efficacy related to multiple factors. When ERMS is diagnosed, it is mostly in the early stage, and the treatment method is mostly surgery plus chemotherapy with or without radiotherapy. However, the treatment effect is related to factors such as staging, Intergroup Rhabdomyosarcoma Study (IRS) clinical grouping, COG-STS risk, patient age, and TP53 mutation. There is no clear guideline for the treatment of adult patients.